Effects of low-dose oxygen ions and protons on cardiac function and structure in male C57BL/6J mice. (February 2019) - Seawright, John W; Sridharan, Vijayalakshmi; Landes, Reid D; Cao, Maohua; Singh, Preeti; Koturbash, Igor; Mao, Xiao-Wen; Miousse, Isabelle R; Singh, Sharda P; Nelson, Gregory A; Hauer-Jensen, Martin; Boerma, Marjan
Abstract: Purpose: Astronauts traveling beyond low-Earth orbit will be exposed to high linear-energy transfer charged particles. Because there is concern about the adverse effects of space radiation on the cardiovascular system, this study assessed cardiac function and structure and immune cell infiltration in a mouse model of charged-particle irradiation. Materials and methods: Male C57BL/6 J mice were exposed to oxygen ions ( 16 O, 600 MeV/n at 0.25−0.26 Gy/min to a total dose of 0, 0.05, 0.1, 0.25, or 1 Gy), protons (150 MeV, 0.35−0.55 Gy/min to 0, 0.5, or 1 Gy), or protons (150 MeV, 0.5 Gy) followed by 16 O (600 MeV/n, 0.1 Gy). Separate groups of mice received 137 Cs γ-rays (1 Gy/min to 0, 0.5, 1, or 3 Gy) as a reference. Cardiac function and blood velocity were measured with ultrasonography at 3, 5, 7, and 9 months after irradiation. At 2 weeks, 3 months, and 9 months, cardiac tissue was collected to assess apoptosis, tissue remodeling, and markers of immune cells. Results: Ejection fraction and fractional shortening decreased at 3 and 7 months after 16 O. These parameters did not change in mice exposed to γ-rays, protons, or protons followed by 16 O. Each of the radiation exposures caused only small increases in cleaved caspase-3 and numbers of apoptotic nuclei. Changes in the levels of α-smooth muscle cell actin and a 75-kDa peptide of collagen type III in the left ventricle suggested tissue remodeling, but there was no significant change in total collagen deposition at 2 weeks, 3 months, and 9 months. Increases in protein amounts of cluster of differentiation (CD)2, CD68, and CD45 as measured with immunoblots at 2 weeks, 3 months, and 9 months after exposure to protons or 16 O alone suggested immune cell infiltration. For type III collagen, CD2 and CD68, the efficacy in inducing protein abundance of CD2, CD68, and CD45 was 16 O > protons > γ-rays > protons followed by 16 O. Conclusions: Low-dose, high-energy charged-particle irradiation caused mild changes in cardiac function and tissue remodeling in the mouse.